The Impact of Covid-19 on Intentions to Conduct Online Transactions: The Role of Affective and Cognitive - Uswatun Khasanah; Ulfatun Nikmah; Agung Dwi Nugroho (Universitas Negeri Semarang, 2023)
Purpose : We investigate the effect of affective and cognitive factors on online transaction intention during the pandemic covid-19 period. Method : We used an internet-based survey through Google form distributed directly to Indonesian respondents with the following criteria: (1) users who have made e-commerce purchases; (2) users who have made transactions on online platforms such as Shopee, Lazada, Instagram, and others. The final sample comprised of 253 respondents, dominated by 185 female users. We employed WarpPLS based on Structural Equation Modelling (SEM) for testing our hypotheses. Findings : We find that cognitive factors, such as perceived ease of use, perceived usefulness, and attitudes towards, have positive effect on online transaction intention. Then, the affective factor, such as perceived enjoyment, positively affects the online transaction intention through cognitive processes, but social norm does not influence the online transaction intention. Novelty : Our study contributes to developing literature on Theory Acceptance Modelling (TAM) by highlighting cognitive and affective factors to explain the effect of the pandemic covid-19 on the intention for the online transaction. Keywords : Affective; Cognitive; Intentions; Technology Acceptance Model